Utilization of waste paper ash as supplementary cementitious material in C-25 concrete: Evaluation of fresh and hardened properties. Issue 1 (1st January 2021) - Meko, Bikila; Ighalo, Joshua
Abstract: The aim of this study was to investigate the properties of concrete with waste paper ash (WPA) as cement replacing material. The chemical composition of WPA was reported, and Portland cement was partially replaced with 0%, 5%, 10%, 15%, and 20% of WPA to explore its effect on both fresh and hardened properties of C—25 concrete. The result of this study indicated that the chemical compositions of WPA were not classified as Pozzolanic material. Setting times of blended cement paste with WPA were lengthened and its consistency was also increased. The cement paste with replacement up to 10% showed a normal consistency within the standard range. The workability of concrete was tested immediately after preparing the concrete mix, whereas the compressive strength was tested after 7 and 28 days of curing. The results indicated that the workability of concrete containing WPA decreases as the WPA content increases. This study also revealed that there is a significant improvement in the compressive strength of concrete. Replacement of ordinary Portland cement by WPA up to 10% results in better compressive strength than that of the control mix. An improvement of 5.6% & 1.2% was observed, respectively, when compared with the 28-day compressive strength of the control mix. But the compressive strength decreases as the WPA replacement increases over 10%. Maximum compressive strength of 37.89 MPa was obtained for concrete containing 5% of WPA.